Carbon nanowalls: a new versatile graphene based interface for the laser desorption/ionization-mass spectrometry detection of small compounds in real samples. Issue 27 (4th July 2017) - Hosu, I. S.; Sobaszek, M.; Ficek, M.; Bogdanowicz, R.; Drobecq, H.; Boussekey, L.; Barras, A.; Melnyk, O.; Boukherroub, R.; Coffinier, Y.
Abstract : Carbon nanowalls for small compounds detection by laser desorption/ionization mass spectrometry. Abstract : Carbon nanowalls, vertically aligned graphene nanosheets, attract attention owing to their tunable band gap, high conductivity, high mechanical robustness, high optical absorbance and other remarkable properties. In this paper, we report for the first time the use of hydrophobic boron-doped carbon nanowalls (CNWs) for laser desorption/ionization of small compounds and their subsequent detection by mass spectrometry (LDI-MS). The proposed method offers sensitive detection of various small molecules in the absence of an organic matrix. The CNWs were grown by microwave plasma enhanced chemical vapor deposition (MW-PECVD), using a boron–carbon gas flow ratio of 1200 in H2 /CH4 plasma, on silicon <100> wafer. The hydrophobicity of the surface offers a straightforward MS sample deposition, consisting of drop casting solutions of analytes and drying in air. Limits of detection in the picomolar and femtomolar ranges (25 fmol μL −1 for neurotensin) were achieved for different types of compounds (fatty acids, lipids, metabolites, saccharides and peptides) having clinical or food industry applications. This rapid and sensitive procedure can also be used for quantitative measurements without internal standards with RSDs <19%, as in the case of glucose in aqueous solutions (LOD = 0.32 ± 0.02 pmol), blood serum or soft drinks. Moreover, melamine (63 ± 8.19 ng μL −1 ), a toxic compound, together with creatinine and paracetamol, was detected in urine samples, while lecithin was detected in food supplements.